Identifying barriers to achieving recreational goals in the planning of urban decay laws - newsha akbari; Alireza Andalib; shirin toghyani; mahmood mohamadi (تحقیقات کاربردی علوم جغرافیایی)
The purpose of the present study was to identify legal challenges to the implementation of regeneretional goals in areas of  urban decay, including those that were selected as pilot sites for the implementation of regeneretional goals after the recent laws on regeneretion. In order to investigate the challenges of implementing regeneretional goals, first the theoretical basis of the research is formulated the necessary process in urban decay legislation, then a questionnaire based on the necessary indices in each dimension and based on the opinions of 50 experts from the Organization for Development. Reproductive Company and Friedman's one-sample t-test and analysis of the effect of different dimensions on the realization of regeneretional goals in the laws and by developing the desirable criteria of legal goals based on the views of the professors and Delphi method, content validity of the later rules. The results indicate that measures taken by the redevelopment laws in the Sirus neighborhood have indirectly driven groups of residents to the outskirts of the city. This challenge stems from the imbalance between property rights and citizenship rights and the public interest. The emphasis on land acquisition and liberalization and the implementation of regeneretion projects have neglected the provision of public and collective benefits and created challenges in other social, economic and managerial dimensions, and the failure to achieve regeneretion goals. Therefore, by presenting strategies to strengthen the theoretical and fundamental dimension of the subject of civil rights, the research aims to provide the necessary framework for reforming the legislative process and providing a platform for the implementation of regeneretional goals.